Role of Toll-like receptors 2 and 4 in pulmonary inflammation and injury induced by pneumolysin in mice. - Mark C Dessing; Robert A Hirst; Alex F de Vos; Tom van der Poll (PLoS ONE, 2009)
BACKGROUND:Pneumolysin (PLN) is an intracellular toxin of Streptococcus pneumoniae that has been implicated as a major virulence factor in infections caused by this pathogen. Conserved bacterial motifs are recognized by the immune system by pattern recognition receptors among which the family of Toll-like receptors (TLRs) prominently features. The primary objective of the present study was to determine the role of TLR2 and TLR4 in lung inflammation induced by intrapulmonary delivery of PLN. METHODOLOGY/RESULTS:First, we confirmed that purified PLN activates cells via TLR4 (not via TLR2) in vitro, using human embryonic kidney cells transfected with either TLR2 or TLR4. Intranasal administration of PLN induced an inflammatory response in the pulmonary compartment of mice in vivo, as reflected by influx of neutrophils, release of proinflammatory cytokines and chemokines, and a rise in total protein concentrations in bronchoalveolar lavage fluid. These PLN-induced responses were dependent in part, not only on TLR4, but also on TLR2, as indicated by studies using TLR deficient mice. CONCLUSION:These data suggest that although purified PLN is recognized by TLR4 in vitro, PLN elicits lung inflammation in vivo by mechanisms that may involve multiple TLRs.